Hot development tools not replacing CASE yet. (computer-aided software engineering versus object-oriented technology) - Nash, Kim S (Computerworld, 1993)
There are advantages to keeping the older generation of computer-aided software engineering (CASE) tools despite the fact that they are slower and harder to use than object-oriented programming products. While such products, typified by Gupta Technology's Structured Query Language family and recent market entries such as Powersoft's PowerBuilder, are the fastest applications workbenches on the market, they lack the scalability and the proven blueprint of management and planning features of older CASE tools. CASE products, on the other hand, are weak in terms of desktop modules, betraying their mainframe system origins. With traditional CASE vendors now offering templates to provide some semblance of a structured methodology, and with guidelines for object-oriented programming beginning to emerge, the user is better off utilizing both technologies as required.